2015
DOI: 10.2105/ajph.2014.302322
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stigma and Medical Mistrust in the Routine Health Care Engagement of Black Men Who Have Sex With Men

Abstract: Background Although HIV infections are documented among all race and sexual risk groups, black men who have sex with men (BMSM) are the most affected by HIV in the US. Currently, there is considerable emphasis on the implementation and use of biomedical HIV prevention to slow the HIV epidemic among this group; however, use of biomedical prevention requires engagement in routine medical care – a necessity that has not been met. Methods In order to better understand this shortcoming, we surveyed 544 BMSM (in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
221
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 340 publications
(229 citation statements)
references
References 60 publications
8
221
0
Order By: Relevance
“…For participants in this study, the desire for privacy and confidentiality hindered PrEP discussions with their routine medical providers out of caution that doing so could change the provider's attitudes towards them and impact the quality of care they receive. Perceived stigma in clinical settings may discourage MSM from accessing needed health care services to advance sexual health and overall well-being (Clift & Kirby, 2012;Eaton et al, 2015;Sabin, Riskind, & Nosek, 2015). Experiences may be exacerbated in socially conservative and rural areas where LGBT populations have less access to quality, LGBT-sensitive care (Kano, Silva-Bañuelos, Sturm, & Willging, 2016;Rosenkrantz, Black, Abreu, Aleshire, & Fallin-Bennett, 2016;Whitehead et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For participants in this study, the desire for privacy and confidentiality hindered PrEP discussions with their routine medical providers out of caution that doing so could change the provider's attitudes towards them and impact the quality of care they receive. Perceived stigma in clinical settings may discourage MSM from accessing needed health care services to advance sexual health and overall well-being (Clift & Kirby, 2012;Eaton et al, 2015;Sabin, Riskind, & Nosek, 2015). Experiences may be exacerbated in socially conservative and rural areas where LGBT populations have less access to quality, LGBT-sensitive care (Kano, Silva-Bañuelos, Sturm, & Willging, 2016;Rosenkrantz, Black, Abreu, Aleshire, & Fallin-Bennett, 2016;Whitehead et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Of the men who were currently receiving ART, only about half reported perfect ART adherence. In order to reduce racial HIV disparities, HIV care engagement interventions must consider sociostructural factors that produce suboptimal HIV care engagement outcomes among young Black men living with HIV in conjunction with proximal factors at the dyadic and individual levels [11, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…Understanding and remediating racial disparities in HIV care engagement and treatment among young Black MSM living with HIV require a multilevel approach that captures the complex ways in which individual behaviors, relationship dynamics, community and sociostructural factors interact to produce and perpetuate these disparities [11, 43, 46]. Analyses using multilevel modeling and the actor-partner interdependence model (APIM) can advance our understanding of multilevel factors in HIV care engagement among young Black MSM living with HIV [47].…”
Section: Future Research and Implications For Enhancing Hiv Engagemenmentioning
confidence: 99%
“…For BWSW, both race and sexual orientation can be sources of stigma, and each of these types of stigma has yielded significant negative consequences for physical and mental health. [4][5][6][7] The social sciences field has established a long history of race-based stigma that affects Black people in the United States. 8 This stigma is strongly related to disparities in physical health, 9 as well as in seeking and receiving quality healthcare.…”
mentioning
confidence: 99%
“…Two studies on this topic found that higher rates of medical mistrust are associated with lower levels of engagement in preventive medicine, such as routine wellness appointments, 21 and are a barrier to routine care among Black men who have sex with men. 4 Moreover, race-based medical mistrust (i.e., the belief that a specific racial group will not receive equal and adequate care from the healthcare system) is a well-established barrier to care for Black people 19 ; White adults are, generally, more likely to engage in preventive health services than their non-White counterparts. 22 However, the role of race-based medical mistrust has yet to be examined among BWSW.…”
mentioning
confidence: 99%